City and countryside in late medieval and Renaissance Italy : essays presented to Philip Jones - Jones, P. J. (Philip James); Dean, Trevor; Wickham, Chris, 1950- (Hambledon Press, 1990)
This book brings together challenging new essays from some of the leaders in Italian scholarship in three countries, to show the range of work that is currently being done not only on Florence but also on Naples, Ferrara and Lucca and on the relationship between cities and countryside.